Design and Development of a Cost-Effective Pes Podoscope - Saurabh Pandey; Anupriya Triapthi; Gargi Khare; Ranjeet Kumar (Journal of Prosthetics Orthotics and Science Technology, 2026)
Background: There are various clinical and radiological methods used in clinical practices to identify foot deformity like high arch and flat feet, but there is no simple and affordable method to identify the issue. Aims: The objective of this study was to make it easier for the clinical practitioners in the field of prosthetics and orthotics to identify the person having flat feet or high arch. Methods: Subject was asked to stand on the podscope with a clean foot so that the image formed on the mirror can be examined. Results: The result showed that the impression of the foot clearly reflects whether the foot is having normal, high arch or flat feet. Conclusion: The results of this study concludes that this device will help practitioners to diagnose and prescribe the best suitable intervention for the person affected with flat foot or high arch.